Zur Frage der Einteilung der Klimazonen - Flohn, Hermann (ERDKUNDE, 1957)
As a supplement to a factual (descriptive) classification of climates, the author considers a genetic classification as significant, both from the physical and didactic view-point. Necessarily a genetic classification must be restricted to the major climatic zones, which in teaching should not be neglected in favour of regional and local climates, as usually occurs in practical work. Its establishment, based either on air masses and fronts (Alissow) or on wind and precipitation fields (as suggested by the author), yields broadly corresponding results in comparison. After some remarks about recent maps of genetic climatic zones, the author discusses the significance of the balance of heat, radiation and water for a rational and factual classification on a sound physical basis. Finally, the concept of dynamicclimatic zones is expanded by discussing some regional anomalies of the general circulation as they result from the physical nature of the earth's surface.